2003
DOI: 10.1128/cdli.10.2.278-285.2003
|View full text |Cite
|
Sign up to set email alerts
|

Serological Cross-Reactivities between Antibodies to Simian Virus 40, BK Virus, and JC Virus Assessed by Virus-Like-Particle-Based Enzyme Immunoassays

Abstract: Enzyme immunoassays (EIAs) for detection of serum antibodies to simian virus 40 (SV40), BK virus (BKV), and JC virus (JCV) were developed by using virus-like-particles (VLPs) produced in insect cells from recombinant baculoviruses expressing the VP1 protein of the respective virus. Rhesus macaque sera with neutralizing antibodies to SV40 showed a high level of reactivity in the SV40 VLP-based EIA, and these sera also showed lower levels of reactivity in the BKV and JCV VLP-based EIAs. Rhesus macaque sera negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
136
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 26 publications
9
136
0
Order By: Relevance
“…Data obtained in normal individuals suggest that natural SV40 infection occurs in human populations with a prevalence lower than that of the ubiquitous JCV and BKV (60-90%) (25). It is possible that SV40 is transmitted through contact in the human environment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data obtained in normal individuals suggest that natural SV40 infection occurs in human populations with a prevalence lower than that of the ubiquitous JCV and BKV (60-90%) (25). It is possible that SV40 is transmitted through contact in the human environment.…”
Section: Discussionmentioning
confidence: 94%
“…Contrasting reports have appeared in the literature on the presence of SV40 footprints in humans and its association with human tumors (20)(21)(22). SV40 antibody detection had been attempted in several studies using serologic methods with SV40 virus-like particles (VLPs), but because of high protein homology among the three main polyomaviruses SV40, BKV, and JCV, the results were always affected by some cross-reactivity (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 77%
“…Recently published studies have shown that SV40 reactivity in human sera may be almost entirely a result of cross-reactivity with BKV and JCV antibodies. 24,25,46 Also in the present study, when SV40 VP1 antibodies were measured in the antibody capture assay without precautions to suppress crossreactive BKV and JCV VP1 antibodies they were correlated with BKV and/or JCV VP1 responses.…”
Section: Discussionmentioning
confidence: 95%
“…This may imply that the frequent finding of SV40 DNA fragments in mesothelioma tumors either is caused by enhanced viral replication favored by the disease process, 47 or that it simply stems from contamination. 10,11 The study was designed on the assumption that SV40 in humans induces persistent infections with a continuous and relatively high production of antibodies as it does in monkeys 24 and similar to the serum responses seen with BKV and JCV infections in humans. Antibodies to VP1 are then expected to be a marker of acute or persistent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation